Brucellosis Presenting with Febrile Pancytopenia: An Atypical Presentation of a Common Disease and Review of Brucellosis - Carina Chang; Bryce D. Beutler; Mark B. Ulanja; Chukwudum Uche; Milan Zdrnja (Case Reports in Infectious Diseases)
Brucellosis is a febrile zoonotic disease caused by one of several species of the Gram-negative coccobacillus Brucella. It is endemic to the Middle East, sub-Saharan Africa, and Central America. However, cases have also been reported in the United States. Infection is most commonly transmitted via unpasteurized dairy products or through occupational exposure to livestock. The clinical presentation is highly variable; symptoms may include fever, myalgias, night sweats, weight loss, nausea, and vomiting. Less common features include orchitis, osteomyelitis, and sacroiliitis. In addition, pregnant women who contract brucellosis face a markedly increased risk of miscarriage. A presumptive diagnosis is typically established through correlation of patient history and classic laboratory findings, which include transaminitis, anemia, and leukopenia with relative lymphocytosis. Definitive diagnosis can only be established through isolation of Brucella species from blood or tissues. Treatment involves a prolonged course of multiple antibiotics; six weeks of combination therapy with aminoglycoside or rifampin and tetracycline represents the most common regimen. Healthy individuals who develop brucellosis have a generally favorable prognosis, as the case fatality rate is less than 2%. Nevertheless, early detection and treatment are essential to reduce the risk of long-term sequelae that may result from chronic, indolent disease.